Pengaruh Electronic Word of Mouth, Electronic Service Quality, dan Electronic Trust terhadap Purchase Decision pada Pengguna Shopee di Kota Bandung - Fatmawati, Fatmawati Nurhikmah; Dedy Ansari Harahap; Yudha Dwi Nugraha (UNISBA Press, 2023)
Abstract. This research focuses on electronic word of mouth, electronic service quality, electronic trust, and purchasing decision variables. This study aims to find out how electronic word of mouth, electronic service quality, and electronic trust describe the purchasing decisions of Shopee users in the city of Bandung, as well as to examine and determine the effect of electronic word of mouth, electronic service quality, and electronic trust on purchasing decisions. This research is included in the type of descriptive and verification research with quantitative methods. The sampling technique used is non-probability sampling, namely purposive sampling. The data collection method used in this study was a survey method with a questionnaire as an instrument. The object of this research is the Shopee user community who are domiciled in Bandung City and have made transactions or shopped at Shopee in the last 6 months or 1 year with a total of 250 respondents who were narrowed down based on sampling criteria to 240 respondents. Data analysis used is descriptive analysis and verification, namely by using multiple linear regression analysis, T test, F test, and the coefficient of determination. The results of this study indicate that electronic word of mouth partially has a positive and significant effect on purchasing decisions, electronic service quality has a positive and significant effect on purchasing decisions, and electronic trust has a positive and significant effect on purchasing decisions. Then simultaneously electronic word of mouth, electronic service quality, and electronic trust have a positive effect on purchasing decisions. Abstrak. Penelitian ini berfokus kepada variabel electronic word of mouth, electronic service quality, electronic trust, dan purchase decision. Penelitian ini bertujuan untuk mengetahui bagaimana gambaran electronic word of mouth, electronic service quality, dan electronic trust terhadap purchase decision pada pengguna Shopee di Kota Bandung, serta untuk menguji dan mengetahui pengaruh electronic word of mouth, electronic service quality, dan electronic trust terhadap purchase decision. Penelitian ini termasuk ke dalam jenis penelitian deskriptif dan verifikatif dengan metode kuantitatif. Teknik sampling yang digunakan adalah nonprobability sampling yaitu purposive sampling. Metode pengumpulan data yang digunakan dalam penelitian ini yakni metode survei dengan instrumen kuesioner. Objek pada penelitian ini adalah masyarakat pengguna Shopee yang berdomisili di Kota Bandung dan pernah melakukan transaksi atau belanja di Shopee dalam 6 bulan atau 1 tahun terakhir dengan jumlah 250 responden yang dikerucutkan kembali berdasarkan kriteria sampling menjadi 240 responden. Analisis data yang digunakan adalah analisis deskriptif dan verifikatif yaitu dengan menggunakan analisis regresi linier berganda, uji T, uji F, dan koefisien determinasi. Hasil penelitian ini menunjukkan bahwa electronic word of mouth secara parsial berpengaruh positif dan signifikan terhadap purchase decision, electronic service quality berpengaruh positif dan signifikan terhadap purchase decision, dan electronic trust berpengaruh positif dan signifikan terhadap purchase decision. Lalu secara simultan electronic word of mouth, electronic service quality, dan electronic trust berpengaruh positif dan terhadap purchase decision.